Specialized nutrition for athletes: evaluation of ergogenic action using the principles of evidence-based medicine - Gunina, L. M.; Shustov, Ye. B.; Belenichev, I. F.; Vysochina, N. L.; Golovashchenko, R. V.; Morozova, O. V.; Бєленічев, Ігор Федорович; Морозова, Оксана Валентинівна (Sofia : Pensoft Publishers, 2022)
Abstract. The aim is to form a balanced position regarding the ergogenic characteristics of new sports food products in the modern practice of training highly qualified athletes on the basis of clinical-experimental evaluation of the effectiveness of special purpose real food additives. Materials and methods. Studies were carried out on laboratory animals (36 Wistar rats at the age of 3 months weighing 150–200 g and 16 Svetlogorsk mini-pigs) as well as on 102 high-qualified representatives of cyclic sports (all men aged 19–26) − members of national teams such as swimming (25), cross-country athletics (53), and skiing (24). As a control group, we studied 25 athletes of the same gender (all men), age and qualifications who received a placebo (starch capsules) for a long time during exercise. Placebo-controlled studies have been conducted on laboratory animals and athletes in compliance with the principles of bioethics. Results. It has been established that in the experiment the application of a new specialized food product MioActiv has a positive effect on the physical performance of animals and delays the onset of fatigue, which significantly exceeds the corresponding characteristics in the placebo group. Athletes also showed an increase in speed when passing competitive distances by 18.7–21.4% (p < 0,05), as well as a significant increase in mental endurance indicators (p < 0,05). The approbation of the innovative pre-workout pharmacological nutrient complex Pre-Fuse also showed the high efficacy and safety of this product with a positive effect of increasing the performance and endurance of animals, as well as the parameters of mental performance of athletes in the main groups, in contrast to the data in the placebo control groups. Conclusions. An analysis of the prescription components of new types of ergogenic sports nutrition and the presented results of preclinical and clinical studies conducted on the basis of the evidence-based medicine paradigm regarding the effectiveness of specialized products indicate the complex action of these funds on various aspects of both physical and mental performance. From the materials presented in the article, it can be seen that specialized sports nutrition products of an ergogenic orientation can provide significant assistance in increasing sports results.
Keywords: sport; ergogenic functional nutrition; new dietary supplements; preclinical studies of working capacity parameters; evidence-based medicine